La problemática de la imputación en los procedimientos sancionadores de SUSALUD - García Ascencios, Frank (2024)
The National Superintendence of Health (Susalud) is the specialized technical agency attached to the Ministry of Health, which is in charge of promoting, protecting and restoring the rights to health services, with quality, opportunity, availability and acceptability. In order to fulfill this purpose, Susalud has the sanctioning power, therefore, it manages the administrative sanctioning or trilateral sanctioning procedure against Health Service Provider Institutions (IPRESS), Health Insurance Fund Administration Institutions (IAFAS) and Health Service Provider Management Units (UGIPRESS). However, Susalud has several contingencies in the charging of the accused, a fact that causes the sanctioning procedures to suffer from defects of nullity from the charging stage, affecting the accused and the complainants, who suffer the legal consequences of a bad start of the procedure. This work collects and develops the most frequent errors in the imputation of charges in Susalud.